High doses of riboflavin and the elimination of dietary red meat promote the recovery of some motor functions in Parkinson's disease patients - Coimbra,C.G. (2003)
Abnormal riboflavin status in the absence of a dietary deficiency was detected in 31 consecutive outpatients with Parkinson's disease (PD), while the classical determinants of homocysteine levels (B6, folic acid, and B12) were usually within normal limits. In contrast, only 3 of 10 consecutive outpatients with dementia without previous stroke had abnormal riboflavin status. The data for 12 patients who did not complete 6 months of therapy or did not comply with the proposed treatment paradigm were excluded from analysis. Nineteen PD patients (8 males and 11 females, mean age ± SD = 66.2 ± 8.6 years; 3, 3, 2, 5, and 6 patients in Hoehn and Yahr stages I to V) received riboflavin orally (30 mg every 8 h) plus their usual symptomatic medications and all red meat was eliminated from their diet. After 1 month the riboflavin status of the patients was normalized from 106.4 ± 34.9 to 179.2 ± 23 ng/ml (N = 9). Motor capacity was measured by a modification of the scoring system of Hoehn and Yahr, which reports motor capacity as percent. All 19 patients who completed 6 months of treatment showed improved motor capacity during the first three months and most reached a plateau while 5/19 continued to improve in the 3- to 6-month interval. Their average motor capacity increased from 44 to 71% after 6 months, increasing significantly every month compared with their own pretreatment status (P < 0.001, Wilcoxon signed rank test). Discontinuation of riboflavin for several days did not impair motor capacity and yellowish urine was the only side effect observed. The data show that the proposed treatment improves the clinical condition of PD patients. Riboflavin-sensitive mechanisms involved in PD may include glutathione depletion, cumulative mitochondrial DNA mutations, disturbed mitochondrial protein complexes, and abnormal iron metabolism. More studies are required to identify the mechanisms involved.